E-035 Cranial Radiation Exposure during Cerebral Angiography. (14th July 2013) - Chohan, M; Sandoval, D; Murray-Krezan, C; Taylor, C
Abstract : Introduction: Radiation exposure to patients and personnel remains a major concern in the practice of interventional radiology. Medical personnel using radiation now account for more than half of all radiation workers exposed to man-made sources of radiation. While scatter radiation exposure to the lens of the eye and regions below the neck have been quantified and minimised using a variety of protective equipment, not much literature is available on exposure to the forehead and cranium. Here, we report cranial radiation exposure to the patient, operating interventional neuroradiologist, and circulating nurse during neuro-angiographic procedures in 24 prospective patients in a modern neuro-interventional suite. We also report the effectiveness of wearing a 0.5mm lead equivalent cap in protection against radiation scatter. Methods: Twenty-four consecutive adult interventional neuro-radiology procedures (6 interventional, 18 diagnostic) were prospectively studied for cranial radiation exposures in the patient, interventional radiologist, and circulating nurse at the University of New Mexico Hospital. Radiation exposure data was collected on each case using NAVLAP accredited (National Voluntary Laboratory Accreditation Program) electronic detectors (Instadose™, Mirion Technologies, CA) placed on the temporal scalp facing the radiation source for the operator and nurse (i.e. left temporal scalp of the operator and right temporal scalp of the nurse), while patient exposure was collected using two thermoluminescent dosimeters (TLD-100, Quantaflux, OH) placed on the table top directly under the patients head. The entire study was done by one operator wearing a 0.5mm lead equivalent skullcap (Radpad Protection, Worldwide Innovations & Technologies, Inc., KS). Results: The mean fluoroscopy time for diagnostic and interventional procedures was 8.48 (SD 2.79) and 26.80 (SD 6.57) minutes, respectively, while patient cranial radiation exposure was 198.60 mSv for diagnostic and 991.54 mSv in interventional procedures. The mean radiation exposure to the operator's head was 7.75 mrem (SD 19.62) as measured on the outside of the 0.5 mm lead equivalent protective headgear. This amounts to 0.08mSv per procedure or 150 mSv/year (the deterministic threshold for lens) in high volume centres doing up to 5 procedures a day. When compared to doses measured on the inside of the protective skullcap, there was statistically significant reduction in the amount of radiation received by the operator's skull (overall means 0.58 + 1.61mrem inside vs 7.75 + 19.62 mrem outside the skull cap). Mean cranial exposure to the circulating nurse was 2.92 + 6.09 mrem. Conclusions: Our study suggests that a modern neuro-interventional suite is safe when equipped with proper protective shields and personal gear. However, cranial exposure is not completely eliminated with existing protective devices and the addition of protective skullcap eliminates this exposure to both the operator and support staff. We therefore, strongly suggest routine use of a protective skullcap. Disclosures: M. Chohan: None. D. Sandoval: None. C. Murray-Krezan: None. C. Taylor: None.